Reversible Atrioventricular Block and Junctional Ectopic Tachycardia in Coxsackievirus B3-Induced Fetal–Neonatal Myocarditis without Left Ventricular Dysfunction - Takahashi, Hironori; Tsukamoto, Keiko; Takahashi, Shigehiro; Nakamura, Tomoo; Ito, Yushi; Kaneko, Masahide; Sago, Haruhiko (American Journal of Perinatology Reports, 2011)
We present a case of fetal–neonatal acute myocarditis caused by coxsackievirus B3 infection in a term neonate. The condition manifested as high-grade atrioventricular (A-V) block prenatally. After delivery, various arrhythmias such as high-grade A-V block, ventricular tachycardia, and junctional ectopic tachycardia appeared, and we had difficulty managing these arrhythmias. This is the first report describing a case of acute myocarditis due to coxsackievirus infection presenting with fetal A-V block. This case is also unique in that it is extremely rare that various arrhythmias occur serially in one patient without left ventricular dysfunction.
Keywords: Myocarditis; junctional ectopic tachycardia; fetal atrioventricular block; amiodarone hydrochloride